40. NUTRITIONAL STATUS OF HOSPITALIZED PREGNANT WOMEN AND SOME RELATED FACTORS: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2025)
Aim of review: To demonstrate the nutritional status of pregnant women hospitalized for inpatient care and synthesize related factors.Methods and Literature Overview: This study employs a scoping review design. The review included peer-reviewed articles in both English and Vietnamese, from the following databases: PubMed/Medline, Google Scholar, Cochrane Library, ResearchGate, and by using keywords related to the research issue. Of 1522 identified articles, 13 met the selection criteria and were therefore included in the current study.Results: Nutritional issues that are common among hospitalized pregnant women include malnutrition, overweight, and obesity. Common comorbidities include gestational diabetes, cancer, preeclampsia, and hypertension. Studies ranged from 27% and higher on malnutrition among pregnant women, while overweight and obesity also posed significant challenges, with obesity rates reaching as high as 54.5% in some studies. Poor nutritional status results in several health problems such as anemia and increased risk of gestational diabetes mellitus.Conclusion: The results from this study could form the basis for the design of effective nutritional interventions, enhance the quality of health services for pregnant women in hospitals, and eventually improve public health.
Keywords: Nutritional status; pregnant women; hospitalized; related factors